Implementasi Theory of Planned Behavior terhadap Entrepreneurial Intention: Efek Moderasi Entrepreneurship Education dan Gender - Okto Aditya Suryawirawan; Wiwiek Srikandi Shabrie; Krido Eko Cahyono (University of Merdeka Malang, 2021)
The aim of this study is to analyze the effect of entrepreneurship education on the entrepreneurial intention of college students in Surabaya. Purposive sampling was used towards 220 college students. The criteria of the samples were students who already took entrepreneurship subject for bachelor degree and entrepreneurship practicum for vocational studies. This study used Mann-Whitney U-Test through SPSS and partial least squares through SmartPLS. This study finds: 1) attitude, subjective norm and perceived behavioral control have a positive significant impact towards entrepreneurial intention, 2) entrepreneurship education has a positive significant impact towards entrepreneurial intention,3) entrepreneurship education failed to moderate any of the theory of planned behavior variables effect toward entrepreneurial intention, 4) gender failed to moderate the relationship between entrepreneurship education and entrepreneurial intention, 5) there was no difference on the level of entrepreneurial intention between male and female college students, 6) there was no difference on the level of entrepreneurial intention between bachelor degree and vocational studies students.